Trabecular variant of juvenile aggressive ossifying fibroma of anterior mandible - Manjunatha BS; Nagarajappa Das; Saraswati Naik; Gowramma R (MDPI AG, 2012)
Juvenile ossifying fibroma (JOF) is an expansile intra-osseous lesion of the jaw that emulate odontogenic lesions frequently seen in patients under 15 years of age. They are histologically characterized by the presence of fibrous stromal cells along with mineralized tissues. Clinically, these are characterized by early age of onset, histological patterns, high rate of recurrence and the aggressive local behavior. The differential diagnosis of JOF with other fibro-osseous lesions of the jaw should be made along with an essential microscopic examination and be largely based on the character of the calcified products of the tumor. The purpose of this article is to present a rare clinical case of the trabecular type of JOF and to describe its clinical, radiological and histological characteristics. The clinician should be aware of this type of lesion in order to be able to distinguish this it from other fibrous lesions if encountered in routine practice and for appropriate treatment to be carried out.